Structural insights into the histidine-containing phosphotransfer protein and receiver domain of sensor histidine kinase suggest a complex model in the two-component regulatory system in Pseudomonas aeruginosa. (2020) - Chen, Shao-Kang; Guan, Hong-Hsiang; Wu, Pei-Hsun; Lin, Li-Ting; Wu, Meng-Chun; Chang, Hwan-You
No abstract available